2017
DOI: 10.1002/mdc3.12561
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sex Therapy in the Management of Patients with Parkinson's Disease

Abstract: Background: Patients with Parkinson disease (PD) and their partners report deterioration in their sexual life. Sexual dysfunction (SD), an important and often ignored aspect, is common in PD. Motor and nonmotor symptoms are involved in limiting pleasure and disturbing function. Sexual dissatisfaction is more common in men that in women. Frequently, both patients and partners have SD associated with PD, and both need suitable treatment. These issues need to be evaluated by neurologists or PD nurses and by speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 76 publications
2
13
0
Order By: Relevance
“…This is consistent with previous studies that proved a strong association between PD and erectile dysfunction [6-9, 11-13, 18, 19]. Similar to previous studies [6,9,18,19], our study showed that sexual satisfaction was impaired among men with PD. Several mechanisms of erectile dysfunction in PD were reported, independent of disease severity, including autonomic dysfunction, central dopaminergic deficiency, psychosocial factors, medication side effects, as well as testosterone deficiency [8,20].…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous studies that proved a strong association between PD and erectile dysfunction [6-9, 11-13, 18, 19]. Similar to previous studies [6,9,18,19], our study showed that sexual satisfaction was impaired among men with PD. Several mechanisms of erectile dysfunction in PD were reported, independent of disease severity, including autonomic dysfunction, central dopaminergic deficiency, psychosocial factors, medication side effects, as well as testosterone deficiency [8,20].…”
Section: Discussionsupporting
confidence: 93%
“…Specific gender differences exist in motor symptoms and NMS in early PD [13][14][15]. Then, women are less prone to talk about sexual and genital issues due to societal attitudes [5]. Finally, women were much less represented in our cohort (33% vs. 67%).…”
Section: Discussionmentioning
confidence: 85%
“…Chronic diseases are associated with a profound change in sexual activity and sexual dysfunction is one of the commonest NMS in PD [8]. The goal of treatment of sexual function in PD should not be limited to maintaining full genital functions but, rather, to achieving pleasure and satisfaction, reducing anxiety and concerns, increasing intimate couple communication and reducing relationship tension [1,5]. Our data confirm these theories and should prompt clinicians to broadly address sexual issues not limited to sexual dysfunction in PD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypersexuality is very vexing for patients who have a limited ability to perform. Adjustment of dopaminergic medication can be helpful, but we often refer many of our patients to a sex therapist who can offer counseling and address alternative approaches to intimacy [78].…”
Section: The Urologistmentioning
confidence: 99%